Pengaruh Work-Life Balance Dan Burnout Terhadap Kepuasan Karyawan CV. Mitra Jaya Company Malang - Muhammad Arrozak; Hadi Sunaryo; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis research was conducted at CV. Mitra Jaya Company Malang. The purpose of this study was to examine and analyze the effect of Work-Life Balance, and Burnout, on Employee Job Satisfaction of CV. Mitra Jaya Company Malang.The variables used are Work-Life Balance and Burnout as independent variables, while the Employee Job Satisfaction variable is the dependent variable. The sample used in this study was 53 employees of CV. Mitra Jaya Company Malang uses the proportional stratification random method. Data collection methods by collecting primary and secondary data. The analysis used includes instrument testing, classic assumption tests, normality tests, multiple linear regression, hypothesis testing and coefficient of determination.The results showed that the Work-Life Balance variable significantly affected the Job Satisfaction of employees of CV. Mitra Jaya Company Malang, while the Burnout variable does not significantly influence the Job Satisfaction of employees of CV. Mitra Jaya Company Malang. Keywords: Work-Life Balance, Burnout, and Employee Job Satisfaction